Financialization in emerging Europe - Milka Kazandziska (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2022)
This paper contributes to the financialization literature exploring the dynamics of financialization in eight emerging European economies (EEEs) compared to the Anglo-Saxon countries. Our analysis encompasses the decade before and the years following the financial crisis in 2008, including the latest developments in conjunction with the Covid-pandemic. Hungary, Bulgaria, Croatia, Turkey, and to a lesser extent, Czech Republic and Poland experienced strong financial inflows, and an accumulation of foreign liabilities. Foreign financial flows in Russia were not as significant for the process of financialization, but rather the state itself. In this paper we identify two types of financialization: 'foreign-finance-led' and 'state-led' financialization, where 'foreign-finance-led' financialization is characterized by increase in net capital inflows and subsequently, foreign indebtedness, whereas the government (the state) in the 'state-led' financialization has a predominant role in the financialization process. Most of the EEEs fit the 'foreign-finance-led' financialization, but with a tendency of a significant state involvement in the financial systems during the Covid-pandemic. Based on the analysis of financialization in EEEs, our findings show that EEEs had variegated financialization dynamics. Financialization in the EEEs was less pronounced compared to United States and United Kingdom. Despite this fact, the dynamics of financialization took a significant pace in the EEEs in the years following the financial crisis of 2008, with rising debt levels during the Covid-pandemic.
Keywords: E44; F34; F36; F65; G01; G20; P51; P52; 330; financialization; financial crises; emerging countries; Central Eastern Europe